Penggunaan Bahan Ajar Sejarah Organisasi Muhammadiyah Sebagai Sarana Pembelajaran Sejarah Lokal Pada Siswa SMA - Andris Malae; Yusni Pakaya; Renol Hasan (Jambura History and Culture Journal, 2019)
This study aims to introduce local history teaching materials (modules) to students of SMA Negeri 1 Gorontalo. By using qualitative descriptive methods, this study seeks to explore student’s understanding of the importance of understanding local history conducted into teaching materials. Based on the research finding, students strongly needed local history teaching materials to understanding the history of Gorontalo collectively. From the results of interviews done to history teachers and students, it can be concluded that it is really important to use teaching materials as a companion of textbooks that have been used in the process of learning history. In addition, the results of interviews done to students it is obtained taht there is a complaint of the of textbooks as a learning media of history, without applying a varied learning process.